Application of the Discovery Learning Learning Model in Thematic Learning in Class V Elementary School - Widyanita, Yupiardi Resita (Universitas Sebelas Maret, 2022)
This study discusses the application of the Discovery Learning learning model to thematic learning in grade V elementary schools. The main purpose of this study is to investigate the effectiveness and impact of applying the Discovery Learning learning model in increasing student engagement and understanding in thematic learning. The research method used was classroom action research involving a class V in an elementary school. Data was collected through class observations, interviews with teachers, and student understanding tests. Data analysis was carried out using qualitative and quantitative approaches to measure changes in student engagement and understanding after the application of the Discovery Learning model. The results showed that the application of the Discovery Learning model significantly increased student involvement in thematic learning. The learning process that encourages students to actively seek information, analyze concepts, and solve problems makes learning more interesting and interactive.